Nexo: clima, água, energia e alimento na bacia do Rio São Francisco, Brasil - Silva, Marx Vinicius Maciel da (2024)
Climate change and anthropogenic changes in land use and cover (UCS) in The coming decades may intensify extreme climatic and hydrological events. Added to possible increase in demands for water, these changes can put great pressure on hydrosystems, thus influencing the generation of hydroelectric energy. To evaluate this assumption, it was proposed in this study to investigate the effects of a set of scenarios of climate change, UCS and water consumption in hydroelectric power generation in main reservoirs of the São Francisco River Basin (BHSF), Brazil. A methodology incorporated: i) analysis of the influence of low variability patterns frequency; ii) analysis of the increase in consumptive demands in energy generation hydroelectric power from BHSF reservoirs; iii) concentrated hydrological modeling for generation of flows and future hydroelectric energy with a set of proposed scenarios; and iv) the distributed hydrological modeling, with calibration and validation of the model in different periods with anthropogenic changes in land use and cover. The results showed that the low-frequency variability associated with long-term drought and flood patterns have a pattern associated with phenomena of the Pacific Decadal Oscillation (PDO) and the Atlantic Multidecadal Oscillation (AMO) and added to the increase in demands consumptive energy causes a significant impact on hydroelectric power generation. The conjunction of climate change scenarios and consumptive demands indicated a significant reduction in availability of water, increase in service failures, and reduction in energy generation hydroelectric. Especially at the Sobradinho hydroelectric plant, the reduction ranged from -30% to -50% in the period from 2021 to 2050 compared to the historical period (1971 to 2000). The scenarios changes to the UCS (2000 and 2018) indicated a reduction in flow, because if the UCS (2000) had remained unchanged and the natural vegetation had been maintained, the magnitude of the flow would be greater than in the current scenario.